Analysis of Determinants of Bullying Tendencies among Urban and Rural Adolescents - Muhammad Mushaddiq; Asnawi Abdullah; Farrah Fahdhienie; Marthoenis Marthoenis; Radhiah Zakaria (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bullying is a serious issue that threatens adolescent mental health and shows a high prevalence in Indonesia. This behavior is influenced by various internal and external factors, yet few studies have comprehensively compared bullying tendencies between adolescents in urban and rural settings. Objective: This study aims to analyze the main determinants influencing bullying tendencies among adolescents aged 12–15 years and to examine interregional differences. A quantitative approach with a cross-sectional design was used. A total of 167 students were selected through cluster random sampling from SMP Negeri 1 Banda Aceh and MTsN 6 Montasik. Data were analyzed using logistic regression and multinomial logistic regression tests. The results showed that parenting style, gender, and self-esteem were significantly associated with bullying tendencies. Authoritarian parenting showed the highest influence (Odds Ratio [OR] = 13.78; p = 0.001), followed by permissive parenting (OR = 6.15; p = 0.043), and self-esteem (OR = 8.81; p = 0.001). Gender also contributed, with males having a higher tendency to engage in bullying than females (OR = 2.54; p = 0.085). In contrast, ethnicity, socioeconomic status, nutritional status (BMI), social skills and popularity, and academic achievement showed no statistically significant associations. The study also found that students in MTsN 6 Montasik (rural area) had higher bullying behavior (25.61%) compared to those in SMP Negeri 1 Banda Aceh (urban area) at 12.94%. These findings affirm the importance of appropriate parenting, healthy self-esteem, and sensitivity to gender differences as key elements in bullying prevention efforts.